HIF-2-dependent expression of stem cell factor promotes metastasis in hepatocellular carcinoma. (1st May 2017) - Wang, Xiuchao; Dong, Jie; Jia, Li; Zhao, Tiansuo; Lang, Mingxiao; Li, Zengxun; Lan, Chungen; Li, Xin; Hao, Jihui; Wang, Hongwei; Qin, Tai; Huang, Chongbiao; et al.
Abstract: Stem cell factor (SCF) is a multifunctional cytokine responsible for tumorigenesis and progression. In this study, we report that increased expression of SCF in hepatocellular carcinoma (HCC) patients is highly associated with metastasis and poor prognosis. SCF inhibition with RNAi inhibited HCC cell migration, invasion in vitro, and reduced intrahepatic metastases burden and significantly prolonged survival in a HCC xeograft mouse model. SCF depletion in HCC xeograft decreased the expression of vimentin and increase the expression of E-cadherin, implicating a role for SCF in epithelial–mesenchymal transition. Our data further demonstrated that HCC cells secreted soluble SCF to promote HUVECs angiogenesis. The overexpression of SCF in HCC is regulated by hypoxic conditions through a selective HIF-2α-dependent mechanism. Knocking-down HIF-2α significantly decreased expression of SCF. Chromatin immunoprecipitation and luciferase assay demonstrated that HIF-2α directly induce the transcription of SCF gene through the hypoxia response element in SCF promoter. In conclusion, we demonstrate that the hypoxia microenvironment in HCC up-regulates SCF expression, which in turn promotes angiogenesis and HCC metastasis. Highlights: HIF-2α-dependent expression of SCF promotes angiogenesis and metastasis under hypoxia microenvironment in HCC. We indicate that SCF was up-regulated by hypoxic conditions through a selective HIF-2α-dependent mechanism. The increased expression of SCF promotes tumor cell metastasis and confers worse clinical outcome in HCC patients.